Makna Simbolis Tradisi Maligay Iraw Tengkayu di Kalimantan Utara (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the symbolic meaning of Maligay in the Iraw Tengkayu tradition of the Tidung people in North Kalimantan and its role in representing the cultural values ​​​​that live within the community supporting it. The study used a qualitative approach with cultural ethnography methods. Data were collected through participatory observation, in-depth interviews with traditional leaders and Tidung community members, and documentation studies of ritual practices and cultural artifacts. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions. The results show that Maligay not only functions as a ritual tool, but also contains symbols that reflect the spiritual, social, and cosmological dimensions of the Tidung people. Elements such as the tiered structure, the choice of cloth colors, the number of poles, and the types of offerings represent the harmonious relationship between humans, God, ancestors, and nature. These symbolic meanings demonstrate the Tidung people's worldview that emphasizes balance, gratitude, and togetherness. These findings emphasize the importance of understanding cultural symbols as part of efforts to preserve local traditions and strengthen the cultural identity of the Tidung people amidst the dynamics of social change and modernization.